Changes in stream food‐web structure across a gradient of acid mine drainage increase local community stability - Justin P. F. Pomeranz; Jeff S. Wesner; Jon S. Harding (Ecology, 2020)
Understanding what makes food webs stable has long been a goal of ecologists. Topological structure and the distribution and magnitude of interaction strengths in food webs have been shown to confer important stabilizing properties. However, our understanding of how variable species interactions affect food‐web structure and stability is still in its infancy. Anthropogenic stress, such as acid mine drainage, is likely to place severe limitations on the food‐web structures availabe, due to changes in community composition and body mass distributions. Here, we used mechanistic models to infer food‐web structure and quantify stability in streams across a gradient of acid mine drainage. Multiple food webs were iterated for each community based on species pairwise interaction probabilities, in order to incorporate the variability of realistic food‐web structure. We found that food‐web structure was altered systematically with a 32‐fold decrease in the number of links and a twofold increase in connectance across the gradient. Stability generally increased sixfold with increasing acid mine drainage stress, regardless of how interaction strengths were estimated. However, the distribution of the stability measure, s , for some impacted communities separated into clusters of higher and lower magnitude depending on how interaction strengths were estimated. Management and restoration of impacted sites needs to consider their increased stability, as this may have important implications for the recolonization of desirable species. Furthermore, active species introductions may be required to overcome the internal ecological inertia of affected communities.